The Correlation between Iranian EFL Learners’ Intercultural Sensitivity, Vocabulary Knowledge, and English Language Proficiency - Farzad Alijanian; Fariba Mobini; Parisa Ghasemi (Issues in Language Teaching, 2019)
AbstractThis study aimed to explore any type and level of association between Iranian EFL learners’ proficiency level and their intercultural sensitivity on the one hand, and the possible relation between vocabulary knowledge and sensitivity to cultural differences on the other. To this end, Oxford Quick Placement Test (OQPT) was administered to 220 EFL leaners. Based on the results of this test, a homogenized sample of 150 EFL learners (70 male and 80 female) at intermediate and upper-intermediate levels was selected. Afterwards, the participants took Vocabulary Levels Test (VLT) developed by Nation, and validated by Webb, Sasao, and Balance. Finally, Intercultural Sensitivity Scale (ISS) by Chen & Starosta was administered. The results of Pearson correlation analyses revealed a statistically significant correlation between the participants' proficiency level and their intercultural sensitivity. The results of regression analyses also indicated that language proficiency contributes as much as 55.4 percent to the prediction of level of intercultural sensitivity. Moreover, a significant positive correlation was detected between EFL learners’ L2 vocabulary knowledge and their intercultural sensitivity level. Further, the results revealed that Iranian EFL learners’ L2 vocabulary knowledge can offer contributions up to 17.3 percent to the prediction of intercultural sensitivity level. These findings can offer prominent implications for all practitioners, material developers, and EFL instructors who are primarily preoccupied with linguistic competence. The results can motivate them to consider intercultural sensitivity as a complementary element to EFL learners’ linguistic knowledge, as well as their communicative commands.